2005
DOI: 10.1002/nme.1269
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated convergence in TLM algorithms for the Laplace equation

Abstract: Transmission line matrix (TLM) schemes for the Laplace equation exhibit some curious features. There exist values of TLM parameters where convergence towards the analytical values is very rapid. This phenomenon is first examined using a binary scattering approach. A Fourier analysis of the equivalently bounded diffusion equation does not reveal any features that would account for these observations. However, a similar analysis using the Telegraphers' equation suggests that a TLM model under optimum conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…For any model, the number of time steps required to satisfy the convergence condition drops as expected as t increases but then rises again above an optimum time step length. This behaviour has been noted previously in TLM diffusion models [11]. The increase is associated with the wave-propagation term in the differential equation for the lossy TL which becomes significant at higher t values and leads to wave-like behaviour which takes time to settle down.…”
Section: Convergencementioning
confidence: 68%
See 2 more Smart Citations
“…For any model, the number of time steps required to satisfy the convergence condition drops as expected as t increases but then rises again above an optimum time step length. This behaviour has been noted previously in TLM diffusion models [11]. The increase is associated with the wave-propagation term in the differential equation for the lossy TL which becomes significant at higher t values and leads to wave-like behaviour which takes time to settle down.…”
Section: Convergencementioning
confidence: 68%
“…, and R d (x) satisfy Equations (10), (7), and (8), then the fourth term in Equation (2) becomes (10) and (11) gives the distributed inductance in terms of u…”
Section: The Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the length of the TL) and time are divided into finite increments. Traditionally steady-state solutions have been found by running the scheme until transients reduce to an acceptable level [7,10,11], but a recent paper has shown that they can also be found directly [5]. The first step in modelling a transmission line using TLM is to choose the locations of the nodes at which the solution will be calculated and a time step length, Δt.…”
Section: The Varied Impedance Schemementioning
confidence: 99%
“…The difference between the instantaneous node voltage and the incident voltages leads to pulses being scattered from the node, one to the left (10) and one to the right…”
Section: The Varied Impedance Schemementioning
confidence: 99%